2020
DOI: 10.1038/s41598-020-69014-x
|View full text |Cite
|
Sign up to set email alerts
|

High taurine supplementation in plant protein-based diets improves growth and organoleptic characteristics of European seabass (Dicentrarchus labrax)

Abstract: Plant-based proteins are increasingly being used in aquafeeds, but one of the limitations is taurine deficiency that can be especially detrimental for carnivorous fish. In this study, taurine supplementation in high plant protein diets (low fish meal, 15%) was investigated on the growth performance and fillet organoleptic characteristics of European seabass ( Dicentrarchus labrax ), juveniles (78 ± 0.4 g). Five diets were formulated to contain 0 (C−), 5 (T5), 10 (T10) or 20 (T20) added t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 47 publications
1
8
1
Order By: Relevance
“…Contrary to these studies, Kotzamanis et al (2020) reported that dietary taurine was not a histological change in the liver of European seabass (D. labrax). Also, the authors determined lipid accumulation within the hepatocytes in European seabass fed all experimental diets.…”
Section: Discussioncontrasting
confidence: 61%
“…Contrary to these studies, Kotzamanis et al (2020) reported that dietary taurine was not a histological change in the liver of European seabass (D. labrax). Also, the authors determined lipid accumulation within the hepatocytes in European seabass fed all experimental diets.…”
Section: Discussioncontrasting
confidence: 61%
“…Seven DEGs annotated as cysteamine dioxygenases (enriched in taurine and hypertaurine biosynthesis metabolism) showed increased expression in UV-C treated banana peels as compared to CK. These genes are known for their role in enhanced plant survival under abiotic stresses (Licausi et al, 2011) by increasing the biosynthesis of taurine (Kotzamanis et al, 2020). Hence, it is possible that UV-C treatment affected their expression in order to respond to changes in O 2 levels in peels, since cysteamine dioxygenases have also been shown to be sensitive to O 2 levels (White et al, 2018).…”
Section: B Effect Of Uv-c Treatment On Secondary Metabolites Related Pathwaysmentioning
confidence: 99%
“…The fatty acid profile was evaluated according to the AOCS Official Method Ce 1c-89, while the amino acid composition of the algal biomass was analyzed after acid hydrolysis (6 N, 110 °C, 24 h) and derivatization by AccQ-Tag TM Ultra according to the amino acid analysis application solution (Waters Corporation, Milford, MA, USA), as described by Kotzamanis et al [ 19 ].…”
Section: Methodsmentioning
confidence: 99%